Evaluation of paraoxonase, arylesterase, and homocysteine thiolactonase activities in patients with diabetes and incipient diabetes nephropathy - Ayan Durmu§; Senes Mehmet; Banu-Çayci Ay§e; Soylemez Sibel; Eren Nezaket; Altunta§ Yüksel; Yener-Oztürk Feyza (Journal of Medical Biochemistry, 2019)
Background: The aim of this study is to examine the relationship among the changes in activities of paraoxonase (PON), arylesterase (ARE) and homocysteine thiolactonase (HTLase) enzyme having antioxidant properties and the development of diabetic nephropathy (DN), one of the most common complications of diabetes. Methods: Normoalbuminuric type-2 diabetic patients (Group II, n = 100), microalbuminuric type 2 diabetic patients (Group III, n = 100) and the control group (Group I, n = 100) were included in the study. The age and gender of the patient groups matched with the age and gender of the control group. HTLase, PON and ARE enzyme activities were measured by the spectrophotometric method using a g-thiobutyrinolactone, paraoxon, and phenylacetate substrates respectively. In this study, an autoanalyzer application was developed in order to measure HTLase enzyme activity for the first time. Results: Serum HTLase, ARE and PON activities of Group III and Group II were significantly low compared to HTLase, ARE and PON results of Group I (p<0.05). Conclusions: Based on our results, PON, ARE and HTLase enzyme activities were found to be decreased due to the increase in the degree of DN.